The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/ta.0000000000001683
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional analysis of neutrophil-to-lymphocyte ratio (NLR) in patients with severe hemorrhage: A new mortality predictor value

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…Duchesne j. et al hypothesized that the NLR would be a prognostic indicator of mortality in this population. At the end of their study, they found that NLR is strongly associated with early mortality in patients with severe hemorrhage managed with massive transfusion protocol [10].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Duchesne j. et al hypothesized that the NLR would be a prognostic indicator of mortality in this population. At the end of their study, they found that NLR is strongly associated with early mortality in patients with severe hemorrhage managed with massive transfusion protocol [10].…”
Section: Discussionmentioning
confidence: 97%
“…Recently, NLR, which is considered as a strong visual fi eld of infl ammation, has been shown in many studies that can be used to predict prognosis in many diseases such as cancer, cardiac, autoimmune [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. NLR is the ratio of absolute neutrophil count to the absolute lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study had found that a trajectory of increasing NLR over the first 48 h of admission is associated with the development of organ failure among male trauma patients [10]. Another study realizes that NLR is strongly associated with early mortality in trauma patients with severe hemorrhage managed with multi-transfusion protocol (MTP) [11]. According to Dilektasli et al who demonstrated the prognostic role of NLR at days 2 and 5 in predicting hospital deaths in trauma patients, in contrast, the NLR in the first 24 h was not useful for predicting outcomes when compared with the next days in the surgical intensive care unit [12]; in this study, hospital days 2 and 5 revealed optimal cutoff values of 8.19 and 7.92, corresponding to a sensitivity and specificity of 70.8% and 61.9% and 75.6% and 66.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fundamental meaning of these ratios, reflecting an inflammatory load, they are frequently reported and tested as prognostic factors in several medical disciplines. Numerous publications (only a few recent articles are quoted) investigated these measures in cardiology [ 1 ], oncology [ 2 ], surgery [ 3 ], and gastroenterology [ 4 ], often incorporating them into the prognostic algorithm [ 5 8 ]. In the gynecology-related literature, NLR and PLR were evaluated in gynecological cancers [ 9 ] and in reproductive morbidities such as ovarian hyperstimulation syndrome [ 10 ], premature ovarian insufficiency [ 11 ] and endometriosis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%